(untitled) (Szociológiai Szemle, 2024)
This paper analyses from the point of view of historical sociology the weakening of the position of the traditional gypsy occupations. In the period of extensive industrialization the unemployment of the gypsies could also be elimenated, but the gypsies became a marginal stratum among the community workers of the heavy industry. Presently the mounting unemployment affects primarily this stratum and the social tensions surrounding the gypsies are also mounting.